Confined jet array impingement cooling with spent flow distraction using NEPCM slurry. (October 2016) - Zhang, C.Y.; Wang, T.; Chen, D.H.; Hong, F.J.; Cheng, P.
Abstract: The confined jet array impingement cooling with spent flow distraction using nano-encapsulated phase change material (NEPCM) slurry (or nanofluids) is investigated numerically using a homogeneous model, based on effective thermophysical properties of the slurry. The NEPCM slurry consists of the carrier fluid of polyalphaolefin (PAO) and the NEPCM particles with Polystyrene shell and paraffin core. The jet impingement cooling of a slot jet array with jet width of 100 μm, confinement height of 300 μm, and jet-to-jet distance of 400 μm is investigated numerically under conditions of different jet velocities, inlet temperatures, particle volumetric concentrations, as well as heat fluxes. Unlike MEPCM (micro-encapsulated phase change material) where micro-convection effect plays an important role in heat transfer enhancement, it is found that this effect has little impact on heat transfer of NEPCM because of much smaller particles of NEPCM. There exists an optimal volumetric concentration to achieve the best heat transfer performance for a given jet velocity, and this optimal volumetric concentration at first increases and then becomes saturated with increasing jet velocity in the range of the present study. An optimal inlet temperature, close to (but lower than) the peak of melting curve of PCM, is determined for the maximum heat transfer enhancement; it is found that the higher the jet velocity (when heat flux is fixed) or the lower the heat flux (when jet velocity is fixed), the closer the optimal inlet temperature to the peak of melting curve. The local heat transfer under the exit slot is the lowest because of the formation of a stagnant zone by the head-to-head collision of the two adjacent wall jets, and adding of NEPCM does not change the basic characteristics of local heat transfer, but a little bit extends the low heat transfer region.